ANALISIS KEUNTUNGAN PEDAGANG BUAH DI KELURAHAN TELING KOTA MANADO (Profit Analysis of Fruit Traders in Teling Sub District, City of Manado) - Indira Gilano; Jenny Baroleh; Agnes Estephina Loho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimED to analyze the profits of fruit traders located from the front of the Teling gas station to the front of the Teling Adventist Hospital in Manado City. The research was conducted in August 2020.The data used in this study were primary data and secondary data. Primary data were obtained from 8 respondents (traders) related to this research. The analysis used was profit analysisThe results showed that the total revenue of fruit traders in Teling Sub District, Manado City for one month was Rp. 16,000,000 and a total cost was Rp.12.043.279. This means that traders got a profit of Rp. 3,653,769.